2015
DOI: 10.1016/j.molimm.2014.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Fli-1 controls transcription from the MCP-1 gene promoter, which may provide a novel mechanism for chemokine and cytokine activation

Abstract: Regulation of proinflammatory cytokines and chemokines is a primary role of the innate immune response. MCP-1 is a chemokine that recruits immune cells to sites of inflammation. Expression of MCP-1 is reduced in primary kidney endothelial cells from mice with a heterozygous knockout of the Fli-1 transcription factor. Fli-1 is a member of the Ets family of transcription factors, which are evolutionarily conserved across several organisms including Drosophilla, Xenopus, mouse and human. Ets family members bind D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 42 publications
2
20
0
Order By: Relevance
“…Together, these results indicate that globally reducing FLI1 levels in MRL/lpr mice decreases renal Neu1 and LacCer levels, but likely is not due to FLI1 regulation of Neu1 expression in the kidney. Intense LacCer staining is observed in the mesangial region of human lupus renal biopsies (12) and we here we demonstrate specific LacCer staining in the glomeruli of MRL/lpr mice (Fig. 1C).…”
Section: Resultssupporting
confidence: 70%
See 4 more Smart Citations
“…Together, these results indicate that globally reducing FLI1 levels in MRL/lpr mice decreases renal Neu1 and LacCer levels, but likely is not due to FLI1 regulation of Neu1 expression in the kidney. Intense LacCer staining is observed in the mesangial region of human lupus renal biopsies (12) and we here we demonstrate specific LacCer staining in the glomeruli of MRL/lpr mice (Fig. 1C).…”
Section: Resultssupporting
confidence: 70%
“…MRL/lpr Fli1 +/+ immune cells, including T cells, do not readily migrate to the kidney when transferred into MRL/lpr Fli1 +/− mice (10). Chemokines Ccl2 ( Mcp-1 ), Ccl3 ( Mip-1α ), Ccl4 ( Mip-1β ) and Ccl5 ( Rantes ) are significantly decreased at the message level in the kidneys of MRL/lpr Fli1 +/− compared to Fli1 +/+ mice and FLI1 was demonstrated to regulate the promoter activity of several different cytokine genes in endothelial cells (8, 9, 12, 13). Here we demonstrated that the expression Cxcl9 and Cxcl10 , CXCR3 ligands, also are significantly decreased in the kidneys of MRL/lpr Fli1 +/− compared to the Fli1 +/+ mice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations